HUBUNGAN KELINCAHAN, KECEPATAN DAN KOORDINASI MATA KAKI TERHADAP KEMAMPUAN DRIBBLING ATLET FUTSAL TRENGGALEK - Wulandari, Selfi Desi; Muhammad; Yudhistira, Dewangga; Nugraha, Afif Dwi; Lestari, Bhekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Background: Dribbling ability is a fundamental technical skill in futsal that is strongly influenced by physical components. However, many regional futsal athletes still demonstrate suboptimal dribbling performance,which is assumed to berelated to insufficient agility, speed, and eye-foot coordination. Previous studies have generraly examined these variables separately, leaving a gap in simultaneous analysis. Purpose: This study aimed to determine the relationship between agility, speed, and eye-foot coordination with dribbling ability of futsal athletes in Trenggalek Regency, both partially and simultaneously. Methods: A quantitative correlational design with a cross-sectional approach was used involving 20 male futsal athletes selected through total sampling. Agility was measured using the Illinois Agility Test, speed with a 30-meter sprint test, eye-foot coordination through a wall-passing test, and dribbling ability using a zig-zag dribbling test. Data were analyzed using Spearman Rank correlation at a significance level of 0.05. Results: The findings showed that agility had a significant positive correlation with dribbling ability (ρ = 0.455; p = 0.044), while speed (ρ = 0.291; p = 0.213) and eye-foot coordination (ρ = 0.266; p = 0.256) were not significantly related. Conclusion: Agility is the most influential factor affecting dribbling ability among the variables studied. Implication: Coaches are recommended to prioritize agility training while still integrating speed and coordination exercises to improve overall dribbling performance.